Transespinosa Cavography by Function - Pérez Valdiviezo, Jesús (1970)
Cavography by transespinosa puncture is a new radiological method used to explore the system of the inferior vena cava. The technique involves the injection of water-soluble contrast material within the bone of the spinous process of the last lumbar vertebrae, in order to obtain the normal or pathological radiological imaging of the inferior vena cava . The dye is driven by the system of vertebral venous plexus to the inferior vena cava, showing the close relationship between the vertebral venous circulation and movement of the inferior vena cava. The examination was performed in 15 patients and angiograms were obtained representative system of the inferior vena cava of normal and abnormal characters. Success was achieved in 14 cases . There was a technical fault failure . This method is recommended for your safety in the entire intrinsic disease of the inferior vena cava and intraperitoneal or retroperitoneal disease processes which affect this system.